Efficacy of a conventional inferior alveolar nerve block compared to the Vazirani-Akinosi and Gow-Gates techniques for mandibular anesthesia - Rishabh Shah; Pallavi Kalia; B S Dayanithi; Sunil Kumar Gulia; Rishabh Bhanot; Sasikanth Challari (Wolters Kluwer Medknow Publications, 2021)
Background: The conventional inferior alveolar nerve block (IANB) cannot be employed in clinical scenarios with trismus. In addition, it is a blind procedure, so failure to follow the ideal anatomical landmarks and improper positioning of the needle may result in anesthesia failure. This study evaluated whether the Vazirani-Akinosi (VA) and Gow-Gates (GG) techniques for mandibular anesthesia have superior outcomes in the form of fewer positive aspirations and rapid onset of action, as well as better anesthetic attainment. Objective: The objective of this study was to evaluate the anesthetic efficacy and associated complications of a conventional IANB compared to the VA and GG techniques. Method: The study involved 300 patients divided randomly into three groups of 100 patients each. Group I received mandibular anesthesia through the GG technique, Group II received mandibular anesthesia through the VA technique, and Group III received mandibular anesthesia through a conventional IANB. The onset of action, incidence of positive aspiration, and success of the anesthetic technique were assessed in all patients. Result: The Group II patients showed superior anesthetic success (97%) that was significantly different from the results of Groups I and III (P = 0.0241). The mean value of the onset of anesthesia was longer in Group I than in the other two groups. A significant difference was seen between the GG and VA techniques (P = 0.0001*) and between the GG and conventional IANB techniques (P = 0.0001*). Conclusion: The VA technique is considerably superior to either the GG or the conventional IANB techniques in terms of the onset of action and anesthesia success. Positive aspirations are encountered relatively more frequently with the conventional IANB technique.